Authentic Leadership Practices in Organizations: Development and Validation of Authentic Leadership Practices Scale in Pakistan - Mubashar, Tahira; Fida, Muhammad Kashif (The Journal of Behavioral Science, 2023)
Authentic leadership is a relatively new domain that has received attention from scholars and practitioners from different fields of behavioral science. However, the scarcity of research on authentic leadership in Pakistan and limitations in existing scales call for the development of an indigenous scale to assess authentic leadership practices. Hence, the present multiphase study aimed to develop and validate a sophisticated measure of authentic leadership practices in the specific collectivistic cultural context of Pakistan. In study 1, taking insight from the four-component model of authentic leadership, 13 leaders from academia and industry were interviewed to develop the authentic leadership practice scale (ALPS). In study 2, the 24-item ALPS was administered to 203 leaders for validation of self-form. Overall, confirmatory factor analysis (CFA) supported the four-factor model. The goodness-of-fit indices revealed that the model was consistent with the empirical data (RMSEA= 0.08, SRMR =0.04, CFI = .91, IFI = .91, TLI = 0.90) Preliminary evidence of convergent validity and internal consistencies supported the final 22-item version of the self-form. In study 3, evidence of construct validity was established (n = 151) for the observer form of ALPS using CFA. The goodness-of-fit indices revealed that the model was consistent with the empirical data (RMSEA= 0.08, SRMR = 0.05, CFI = 0.89, IFI = 0.89, TLI = 0.87) with internal consistencies. The present study contributes to research and practices of behavioral sciences by providing a psychometrically sound multidimensional scale of authentic leadership practices that may facilitate the assessment-based development of authentic leadership.